Genome-wide identification and expression profiling analysis of DIR gene family in Setaria italica - Gong, Luping; Li, Bingbing; Zhu, Tao; Xue, Baoping (Frontiers in Plant Science, 2023)
Dirigent (DIR) proteins play essential roles in regulating plant growth and development, as well as enhancing resistance to abiotic and biotic stresses. However, the whole-genome identification and expression profiling analysis of DIR gene family in millet (Setaria italica (Si)) have not been systematically understood. In this study, we conducted genome-wide identification and expression analysis of the S. italica DIR gene family, including gene structures, conserved domains, evolutionary relationship, chromosomal locations, cis-elements, duplication events, gene collinearity and expression patterns. A total of 38 SiDIR members distributed on nine chromosomes were screened and identified. SiDIR family members in the same group showed higher sequence similarity. The phylogenetic tree divided the SiDIR proteins into six subfamilies: DIR-a, DIR-b/d, DIR-c, DIR-e, DIR-f, and DIR-g. According to the tertiary structure prediction, DIR proteins (like SiDIR7/8/9) themselves may form a trimer to exert function. The result of the syntenic analysis showed that tandem duplication may play the major driving force during the evolution of SiDIRs. RNA-seq data displayed higher expression of 16 SiDIR genes in root tissues, and this implied their potential functions during root development. The results of quantitative real-time PCR (RT-qPCR) assays revealed that SiDIR genes could respond to the stress of CaCl2, CdCl, NaCl, and PEG6000. This research shed light on the functions of SiDIRs in responding to abiotic stress and demonstrated their modulational potential during root development. In addition, the membrane localization of SiDIR7/19/22 was confirmed to be consistent with the forecast. The results above will provide a foundation for further and deeper investigation of DIRs.